Elucidation of flux decline phenomenon in ultrafiltration of polydisperse silica solution - N. H., Ramli; C. S., Zakaria; M. S., Mohd Sueb; Sunarti, Abd Rahman; N. E., Badrul Hisham (Institute of Physics Publishing, 2020)
Ultrafiltration (UF) is widely used in water filtration process due to its ability to operate at low pressure with higher permeate flux. However, fouling is one of the constrains usually occurred in UF, especially when involving colloidal material. Colloidal silica widely used as a synthetic form of colloidal foulant to investigate membrane performance. It has a special characteristic which can change the charge around the molecules easily depending on the surrounding condition. This study was aimed to identify the most significant factor contribute to permeate reduction of UF membrane of polydisperse silica solution that could lead to the fouling issue of this membrane. The factors that have been studied were ionic strength, pH, transmembrane pressure, ratio of feed solution and types of membrane used (modified or unmodified). Fractional factorial design was used to investigate the effect of individual factors and also the interaction factors on the reduction of permeate flux by using Design Expert software. The finding from this study revealed that the factors of fouling was related to each other. In determining the rate of permeate flux, the ionic strength, pH and pressure should not be considered separately. The only independent factor affecting the permeate flux was ionic strength. However, the effect was not prominent compared to interaction factors. Also, surface-modified membrane by using Pebax 1657 has shown opposite trend in terms of pH and pressure effect on permeate flux.